Bakhtin’s theory of heteroglossia/intertextuality in teaching academic writing in higher education - Chatterjee-Padmanabhan, Meeta (Journal of Academic Language and Learning, 2014)
Bakhtin’s theory of hetereoglossia, reframed as ‘intertextuality’ by Kristeva in the 1960s, is best encapsulated by Bakhtin’s quotation, “Each word tastes of a context and contexts in which it has lived its socially charged life; all words and forms are populated by intentions” (Bakhtin, 1981, p. 293). The concept of intertextuality draws on Bakhtin’s (1981, 1986) theory of heteroglossia in literature which has been appropriated by scholars outside literary studies to enrich areas such as linguistics and education. Fundamental to the concept of intertextuality is the idea of genres. The notion that genres are the “drive belts” (Bakhtin, 1986, p. 65) of society and play a vital role in communication has resonated with many applied linguists and educators. Johns (2002, p. 3) observes that genre pedagogy marks ‘a major paradigm shift’ in literacy teaching. Hyland (2007) hails genres as one of the most important and influential concepts of language. Several recent books on genre (see Bawarshi & Reiff, 2010; Tardy, 2009) and an entire volume of the Journal of Second Language Writing devoted to genre pedagogy has reinforced its centrality in teaching academic writing. This paper identifies four areas that have been influenced by Bakhtin’s theory of heteroglossia and genre: plagiarism in student writing; citation practices; Appraisal theory in Systemic Functional Linguistics and finally, genre pedagogy that focuses on the teaching of academic texts from primary school to doctoral writing.